The impact of Artificial Intelligence on Management Decision-Making: Analyzing the Role of Data Analytical Skills and Entrepreneurial Orientation - Mohammed Yamani, Amal; Yusuf, Nadia; Arif Al-Shabrawi, Hattan (European Journal of Sustainable Development, 2025)
Artificial Intelligence (AI) is changing how businesses function and plan by being incorporated into managerial decision-making processes. This study focuses on how AI affects managerial decision-making, emphasizing the importance of data analysis abilities and an entrepreneurial orientation. Despite the potential of AI, existing research often overlooks the critical interplay between these skills and orientation in optimizing AI utilization. This gap highlights a significant drawback in current understanding: insufficient emphasis is placed on the human factors that drive effective AI adoption. This study proposes a novel approach that integrates data analytical skills and entrepreneurial orientation into AI-driven decision-making frameworks. This study aims to bridge the gap in research by developing a comprehensive theoretical framework and providing practitioners with practical guidance. Using a mixed-methods approach, the methodology combines quantitative surveys with qualitative case studies to create a reliable dataset from various business contexts. The results demonstrate that companies with strong data analytical capabilities and a pronounced entrepreneurial orientation are more adept at leveraging AI technologies for strategic decision-making. Quantitative analysis reveals significant correlations between these factors and improved decision-making outcomes, while qualitative insights from case studies highlight practical examples of successful AI integration. Overall, this study underscores the importance of cultivating both data analytical skills and an entrepreneurial mindset to harness the full potential of AI in management. The findings provide valuable recommendations for businesses and educational institutions, emphasizing the need for targeted skill development and innovative thinking. Keywords: Artificial Intelligence, Management Decision-Making, Data Analytical Skills, Entrepreneurial Orientation, AI Integration, Strategic Decision-Making